(untitled) (The Review of Diabetic Studies, 2025)
Background: Prolonged mechanical ventilation (MV) in critically ill patients is associated with significant morbidity, including ventilator-associated pneumonia, delirium, and extended ICU stays. Optimizing sedation and analgesia during the weaning process is critical to reduce complications and facilitate safe extubation. Objective: This systematic review aimed to synthesize empirical evidence on sedation and analgesia protocols for MV weaning, evaluating their effects on ventilation duration, extubation success, and ICU outcomes. Methods: Following PRISMA 2020 guidelines, eleven randomized and observational studies published between 2010 and 2025 were reviewed. Databases searched included PubMed, Scopus, Embase, and Web of Science. Inclusion criteria encompassed adult ICU patients receiving sedation or analgesia interventions during MV weaning Results: Studies demonstrated that protocolized sedation strategies, including daily interruption and nurse-led protocols, significantly shortened MV duration and ICU stays. Agents like dexmedetomidine, ciprofol, and remimazolam showed superior sedation control, reduced delirium, and improved patient–ventilator synchrony compared to propofol and midazolam. Sequential sedation (midazolam–dexmedetomidine) and analgesic innovations (esketamine, oliceridine) enhanced hemodynamic stability and reduced norepinephrine use. Conclusion: Evidence supports that structured sedation and analgesia optimization improves weaning outcomes, shortens ICU length of stay, and enhances patient safety. Integration of standardized, protocol-driven sedation—potentially supported by AI and interdisciplinary teams—should be prioritized in ICU practice.